trig

posted by .

Factor each expression:
cos^2x- 2cosx+1

4cos^2x-1

  • trig -

    call z = cos x

    z^2 -2z +1
    (z-1)(z-1)
    so
    (cosx-1)(cosx+1)


    4z^2-1
    (2z-1)(2z+1)
    (2cosx-1)(2cosx+1)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Trig

    prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
  2. Math - Trig - Double Angles

    Prove: cos4x = 8cos^4x - 8cos^2x + 1 My Attempt: RS: = 4cos^2x (2cos^2x - 1) + 1 = 4 cos^2x (cos2x) + 1 LS: = cos2(2x) = 2cos^2(2x) - 1 = (cos^2(2)) - cos^2(2x)) - 1 ----- Prove: 8cos^4x = cos4x + 4cos2x + 3 My Attempt: RS: = cos2(2x) …
  3. Math - Solving for Trig Equations

    For the following equation, why cannot I not solve it?
  4. Math - Solving Trig Equations

    What am I doing wrong? Equation: sin2x = 2cos2x Answers: 90 and 270 .... My Work: 2sin(x)cos(x) = 2cos(2x) sin(x) cos(x) = cos(2x) sin(x) cos(x) = 2cos^2(x) - 1 cos(x) (+/-)\sqrt{1 - cos^2(x)} = 2cos^2(x) - 1 cos^2(x)(1 - cos^2(x))
  5. RESPONSE to PreCalc Question

    h t t p : / / w w w . j i s k h a . c o m / d i s p l a y . c g i ?
  6. trig

    cos@-4SIN@=1 then sin@+4cos@=
  7. Trig

    Prove (cos^2t+4cos^2+4)/(cost+2)=2sect+1)/sect
  8. Trig

    (cos^2t+4cos^2+4)/(cost+2)=(2sect+1)/sect
  9. Trig

    Factor 4cos^2x+4cosx-1=0
  10. TRIG

    Factor 4cos^2x+4cosx-1=0

More Similar Questions